2005
DOI: 10.1186/1471-2164-6-121
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics and expression analysis of the Corynebacterium glutamicum fpr2-cysIXHDNYZ gene cluster involved in assimilatory sulphate reduction

Abstract: Background: Corynebacterium glutamicum is a high-GC Gram-positive soil bacterium of great biotechnological importance for the production of amino acids. To facilitate the rational design of sulphur amino acid-producing strains, the pathway for assimilatory sulphate reduction providing the necessary reduced sulfur moieties has to be known. Although this pathway has been well studied in Gram-negative bacteria like Escherichia coli and low-GC Gram-positives like Bacillus subtilis, little is known for the Actinomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…thermopropionicum has a gene cluster that encodes transporters and enzymes for sulfur anions (Supplemental Table S5). Its gene content is similar to those annotated as assimilatory sulfate-reducing gene clusters in Clostridium acetobutylicum (AE001437) and other bacteria (Rückert et al 2005). On the other hand, gene clusters considered to be necessary for dissimilatory sulfate reduction, such as those for transmembrane electron transport complexes (Haveman et al 2004), are not found in P. thermopropionicum.…”
Section: Metabolismmentioning
confidence: 65%
“…thermopropionicum has a gene cluster that encodes transporters and enzymes for sulfur anions (Supplemental Table S5). Its gene content is similar to those annotated as assimilatory sulfate-reducing gene clusters in Clostridium acetobutylicum (AE001437) and other bacteria (Rückert et al 2005). On the other hand, gene clusters considered to be necessary for dissimilatory sulfate reduction, such as those for transmembrane electron transport complexes (Haveman et al 2004), are not found in P. thermopropionicum.…”
Section: Metabolismmentioning
confidence: 65%
“…The siroheme prosthetic group is known to be essential for the function of sulfite-reductases, which convert sulfite (derived from sulfate) to sulfide [67]. Thus, cluster 4 proteins may be involved in the uptake of sulfate or other sulfur-based compounds, a suggestion supported by sequence similarity between cluster 4 proteins and CysZ of Corynebacterium glutamicum , a putative sulfate transporter [16]. …”
Section: Resultsmentioning
confidence: 99%
“…A putative sulfate uptake porter termed CysZ (TC# 2.A.102.6.1) was also shown to belong to the TSUP family. As for TauE, its mechanism of action is unknown [16]. Yet another homologue, SafE1 (TC# 2.A.102.2.2), was proposed to be a sulfoacetate exporter [17].…”
Section: Introductionmentioning
confidence: 99%
“…cysZ is a conserved, non-essential gene that encodes an inner membrane protein involved in sulfate transport [35], [36]. It is not surprising that sulfate transporter proteins would be highly abundant as this is a key nutrient for cells during all phases of growth.…”
Section: Discussionmentioning
confidence: 99%